Evaluation of Fertilizer Inventory Management of PT. ABC Using EOQ Method - Chella Masquita Febilia; Dyah Febriantina Istiqomah (Jurnal VOK@SINDO, 2016)
The plentiful company inventories are associated with the high storage and order cost. However, the limited number of inventories results in the lack of supply shortages that could hamper the process of buying and selling on trading companies and loss of profits. During this time, PT. ABC has ordered fertilizer X and Z using rough estimates. Thus, the company sometimes has excessive or even limited amount of fertilizer X and Z which results in providing unsatisfactory service for the customers’ demand. This research was aimed to evaluate the inventory management of fertilizer X and Z at PT ABC using EOQ (Economic Order Quantity) method. Data collection was done through observation and interviews with the company. Data were analyzed using the EOQ method. The results showed that the inventory management by using the EOQ method is more efficient than the inventory management policy that has been done by the company. This is because by using the EOQ method the frequency of order is lower so the order cost will be low as well. Therefore, the company should consider using EOQ method because this method can help the company to get the optimal quantity of inventory purchases with a minimum order fee compared to the previous company policy.